Assessing the Impact of Terminalia arjuna Plant Extracts on the Growth and Sporulation of Trichoderma harzianum, Aspergillus niger and Penicillium chrysogenum - A.K. Shamla; A. Vijaya Chitra (Journal of Pure and Applied Microbiology)
This research investigates the impact of ten medicinal plant extracts on the growth and sporulation of prominent industrial fungal strains-Trichoderma harzianum, Aspergillus niger, and Penicillium chrysogenum. The phytochemical analysis revealed a diverse array of bioactive compounds, hinting at potential antimicrobial and antioxidant properties. Particularly, Terminalia arjuna consistently exhibited positive effects on fungal growth, implying a lower degree of antifungal activity, whereas Phyllanthus emblica showed variable impacts. These findings were supported by radial growth rates, highlighting Terminalia arjuna’s consistent stimulation of fungal growth. Sporulation indices and spore production further affirmed substantial sporulation in Terminalia arjuna. Comparative analyses with previous studies emphasized the unique characteristics of this extract. In conclusion, Terminalia arjuna shows distinct characteristics compared to other samples, indicating the need for additional investigation, suggests promising applications in both industrial and medicinal contexts, warranting further exploration for optimal utilization.